Use of behavioural activation to manage pain: a systematic scoping review - G Lorimer Moseley; Marianne Gillam; Martin Jones; Sandra Walsh; Richard John Gray; Trevor Barker; Tesfahun Eshetie; Kate M. Gunn; Kham Tran (BMJ Open)
Background Behavioural activation (BA) is an effective treatment for depression; however, it is unclear if it can be used to manage pain.Objectives To conduct a scoping review of primary research that reported using BA to support people living with chronic pain to understand how BA had been used in relation to pain. In addition, we wanted to understand whether there were any reported changes in that pain, and how and who delivered BA.Eligibility criteria Primary research published in English.Sources of evidence We searched seven databases MEDLINE, Ovid Embase, Ovid Emcare, PsycINFO, CINAHL, Scopus and Web of Science, for primary research. No initial date limit was used with the date the searches were conducted used as the end date limit (1 July 2021).Charting methods A customised data extraction table was developed, piloted and used.Results 551 papers were screened for inclusion, with 15 papers included in our review. Studies were conducted in North America and in Canada. These included three case studies, nine uncontrolled trials and three randomised controlled trials. Only two studies reported pain as the primary outcome. BA was applied across a range of pain related conditions. The dose of BA ranged from 3 to 16 sessions. Duration of treatment was 3 weeks to 12 months. Most studies reported reductions in pain following exposure to BA.Conclusion BA has the potential to reduce pain. Caution needs to be exercised in the interpretation of these findings as a high risk of bias was observed in most studies. High-quality research is required to test if BA is an effective intervention for chronic pain.